Black Brant Branta bernicla nigricans forage at both tides on Humboldt Bay, California, USA - Elkinton, Elizabeth; Lo, Long; Black, Jeffrey M. (Wildfowl, 2013)
Black Brant Branta bernicla nigricans arrive at their breeding grounds in arctic and subarcticÂ North America and eastern Russia in spring, a time when food resources areÂ limited. They rely largely on energy stores, acquired at staging sites, for migration andÂ to support egg laying and incubation. In California, Humboldt Bay is the mostÂ important staging site for Black Brant due to the abundance of Common EelgrassÂ Zostera marina along its shores. Access to Common Eelgrass has been assumed to beÂ limited to low tides, when the plants are reachable, and that little feeding occurs atÂ higher tides. We tested this assumption by quantifying Black Brant foraging behaviourÂ throughout the tidal cycle, including in relation to factors that contribute to theÂ occurrence of detached Common Eelgrass leaves, which float to the surface and thusÂ become available to the birds at higher tides. Throughout the winter and springÂ periods (Januaryâ€“April 2011) Black Brant at Humboldt Bay foraged directly onÂ Common Eelgrass beds during low tides and continued to feed on drifting leavesÂ during higher tides. They switched from bed-feeding to drift-feeding at a mean tideÂ height of 0.9 m. On average, 48% of flock members typically fed when CommonÂ Eelgrass beds were reachable during low tides, with 24% of birds feeding on driftingÂ eelgrass during higher tides. The prevalence of drift-feeding declined as the tide levelÂ increased in the bay, ranging from 35% of birds at 1 m tides to 10% at 2.5 m tides.Â The amount of drifting Common Eelgrass available to Black Brant increased withÂ higher maximum wind speeds and greater tidal range in the previous 24 h, and withÂ greater numbers of Black Brant on the bay. By providing current information aboutÂ foraging strategies and the use of high-tide feeding opportunities, this study canÂ inform future projections of the carrying capacity of Humboldt Bay for stagingÂ Brant. This is particularly important in light of projected future impacts of sea levelÂ rises on food availability at staging habitats along the Pacific Flyway.